Analisis Analisis Dampak Perubahan Iklim Terhadap Kesehatan Mental Anak di Sekolah Dasar Negeri Setu Kota Tangerang Selatan Tahun 2022 - Ernyasih; Geia Celia Al'Ariq; Suherman (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2023)
Climate change is an environmental phenomenon that threatens global health, impacting mental health and emotional well-being. According to Riskesdas 2018, the prevalence of mental health disorders in Indonesia at the age of ≤ 15 years who suffer from mental illnesses such as symptoms of depression and anxiety has increased from 6% to 9.8%. This study aims to find out the impact of climate change on child mental health in the Setu State Department of Southern Tangerang City in 2022. The method used is descriptive, presenting the variable studied without comparing variables with a sample of 76 respondents in the Sotu State Department implemented from December 2022 to January 2023. The results of the study showed that there was a picture of climate change on mental health, with 75 percent mental health disorders, 27.6 percent cognitive impairment, 32.9 percent anxiety, 26.3 percent depressive and somatic disorder, and 19.7 percent energy loss disorder out of 76 respondents. There is an overview of the impact of climate change on children's mental health in the state of Setu, and some students suffer from cognitive impairment, anxiety disorder, depression, somatic disorder, and energy depletion disorder based on frequency distribution. Researchers are expected to advise students to maintain and address various mental health threats and better understand climate change and its impact on mental health, for schools to provide character education, counseling guidance, and climate impact education.